SKD61 열간합금강의 레이저 표면 합금화 경화처리 공정에서 SKH51 분말 송급속도에 따른 균열 형성에 대한 고찰 - 최성원; Seong-won Choi; 이광현; Kwang-hyeon Lee; 서정; Jeong Suh; 오명환; Myeong-hwan Oh; 강정윤; Chung-yun Kang (대한금속·재료학회지, 54(3), 2016)
A laser surface-melting alloying process using a laser beam is a new surface-hardening process of obtaining an alloying layer that melts the surfaces of substrates and alloying powder at the same time. This study used SKD61 hot die steel as a substrate and SKH51 powder as an alloying powder. The laser beam speed and the laser power were fixed at 70 mm/sec and 2 kW. The power feeding rate was changed from 0 rpm to 6 rpm (step: 1 rpm). The alloying layer showed high hardness (710~830 Hv), but cracks occur at a high powder feeding rate. Cracks occur at more than 5 rpm, and the lengths of cracks become longer as the powder feeding rate increases. Moreover, cracks were observed at the dendrite boundary, and dendrite protrusions were observed on the fracture surfaces. As the powder feeding rate increases, the concentration of the Mo, V, and W in alloying layer increase. The liquidus and solidus temperatures decreased by as much as 6 ℃ and 26 ℃. As a result of calculating the aspect ratio (penetration depth/width) of the molten zone, it was found that there is no difference as the powder feeding rate increases. Therefore, strain by solidification contraction was constant with an increase in the powder feeding rate, but cracks occur, and the number of cracks increases because the solidus temperature decreases and the ductility of alloying layer reduces.